The development of entrepreneurship in hotel business of Russia - O. V. Shataeva; V. A. Nikityuk (Путеводитель предпринимателя)
In the article the basic directions of development of entrepreneurship in hotel business of Russia. Analyzed this modern phenomenon of economy - hotels, hostels, motels and other budget accommodation.